Economic mimicking and social asynchrony of cooperativism in Colombia - Monsalve Z., Alveiro (Cooperativismo & Desarrollo, 2014)
Because cooperativism originated in the midst of an economic and social logic with profound inherent contradictions —the logic of the capitalist system— it is hard for it to differentiate itself in practice and rationale. The logic of the capitalist model has its own identity, as does the logic of the cooperative mod- el. To exist in practice, however, cooperativism must mimic individualistic and competitive economic practices within the capitalist system. This situation diminishes the identity and social effectiveness of cooperativism, and generates asymmetry as an innovative proposal with regard to the socio-economics of solidarity. This study concludes that to overcome this mimicking and asynchrony, cooperativism must truly be an autonomous system of sustainable development in the world.